Modelling of heat transfer through bus body - Shetty, Shisheer; Kumar, Udhaya Bhaskhar (My University, 2023)
Electric buses are catching up and form a major part of the public transport system in major cities. The sustainability and low environmental impact of these buses make them a good option for use in major cities. However, efficiency is a key factor that makes them an attractive option. The HVAC system in these buses, responsible for making rides comfortable, is one of the largest energy consumers. It is essential to study the flow of heat in the bus to optimize the usage of these systems. A realistic simulation that accounts for all types of heat transfer could provide a much higher level of accuracy and give us valuable insight. In this Master Thesis, a method was developed for simulating the interior climate and the heat transfer that happens through the bus’s body. The methodology used a pseudo-transient model with a co-simulation of STAR-CCM+ and TAITherm. Multiple CFD steady-state simulations are run on STAR-CCM+ to account for the convection part of the heat transfer. Steady-state and transient simulations run in TAITherm simulate the conduction and radiation in the bus. These two models are coupled at multiple instances to simulate the transient physics while reducing the heavy computational times involved in transient CFD simulations. This approach has advantages and shortcomings, as will be discussed further in this thesis. The model was tested for a weather condition of -5 °Celsius.
Keywords: Electric buses; heat transfer; co-simulation; CFD; HVAC